2013
DOI: 10.1038/ncomms3611
|View full text |Cite
|
Sign up to set email alerts
|

Probing water micro-solvation in proteins by water catalysed proton-transfer tautomerism

Abstract: Scientists have made tremendous efforts to gain understanding of the water molecules in proteins via indirect measurements such as molecular dynamic simulation and/or probing the polarity of the local environment. Here we present a tryptophan analogue that exhibits remarkable water catalysed proton-transfer properties. The resulting multiple emissions provide unique fingerprints that can be exploited for direct sensing of a site-specific water environment in a protein without disrupting its native structure. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 53 publications
5
103
1
Order By: Relevance
“…Moreover, replacing C(2) by an electron-withdrawing N(2) nitrogen, we have reported a wellresolved proton-transfer emission in 500 nm for (2,7-aza)Trp in neutral water (vide supra). 18 The prohibition of protonation on the (2,7-aza)Trp tautomer in the excited state correlates well with a pK a * of 5.9 of its tautomer analogue 7M(2,7-aza)Trp (Figure 1 and Table 1) example, we then added a substituent CF 3 at C(2) of 7AI to form 2CF 3 AI (see Figure 1), which also gives a well-resolved tautomer emission at 500 nm ( Figure 6). The existence of tautomer and hence the prominent green emission implies the low pK a * (≪7) of its conjugate acid.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, replacing C(2) by an electron-withdrawing N(2) nitrogen, we have reported a wellresolved proton-transfer emission in 500 nm for (2,7-aza)Trp in neutral water (vide supra). 18 The prohibition of protonation on the (2,7-aza)Trp tautomer in the excited state correlates well with a pK a * of 5.9 of its tautomer analogue 7M(2,7-aza)Trp (Figure 1 and Table 1) example, we then added a substituent CF 3 at C(2) of 7AI to form 2CF 3 AI (see Figure 1), which also gives a well-resolved tautomer emission at 500 nm ( Figure 6). The existence of tautomer and hence the prominent green emission implies the low pK a * (≪7) of its conjugate acid.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…This prominent proton-transfer emission thus serves as a unique fingerprint and has been successfully exploited for direct sensing of a sitespecific water environment in the human thromboxane A2 synthase (hTXAS) without disrupting its native structure. 18 We also noticed that upon removing the α-amino acid part from (2,7-aza)Trp, forming 2,7-diazaindole, similar proton-transfer emission was also resolved, which is in stark contrast to the lack of tautomer emission for 7AI in water. From the fundamental point of view, a core issue is thus raised regarding factors that govern the water-catalyzed ESPT and hence the resolution of proton-transfer tautomer emission.…”
Section: ■ Introductionmentioning
confidence: 87%
“…Essentially, sensing hydration water in proteins occurs without disrupting their native structures (Shen et al 2013). Using this property, it was found that RNase T1, a small protein composed of 104 amino acid residues, exhibits the structure fluctuating between the two loop-close and loop-open forms differing by exposure to water of a single residue Trp59 (Chao et al 2014), see Fig.…”
Section: Responsive Analogs Of Amino Acids and Nucleic Acid Basesmentioning
confidence: 98%
“…4.17) has been recently synthesized and suggested for probing the hydration of particular sites in proteins (Shen et al 2013). This artificial amino acid can be recognized by biosynthetic Whereas Trp emits fluorescence in the near-UV with polarity-dependent band maxima at ~330-350 nm, (2,7-aza)Trp has two additional fluorescence bands extending to the visible that appear due to water-catalyzed proton transfer reaction.…”
Section: Responsive Analogs Of Amino Acids and Nucleic Acid Basesmentioning
confidence: 99%
“…4.3 , 2,7-azatryptophan is of value not only as noncanonical artifi cial fl uorescent Trp analog but also as amino acid that can be incorporated into proteins instead of Trp by normal protein synthetic machinery (Shen et al 2013 ). Moreover, in addition to emission spectrum at ~340 nm (which is common for indole derivatives) it exhibits additional band in the visible, at ~500 nm.…”
Section: Co-synthetic Incorporation Of Fluorescence Dyesmentioning
confidence: 98%